Upcoming Events (Pharmacognosy Communications)
January 19-20, 2026 International Conference on Pharmacognosy, Phytochemistry and Natural Products. Mandalay, Myanmar. https://waset.org/ pharmacognosy-phytochemistry-and-natural-products-conf erence-in-january-2026-in-mandalay February 12-13, 2026 International Conference on Natural Products and Drug Discovery. Kuala Lumpur, Malaysia. https://waset.org/ natural-products-and-drug-discover y-conference-i n-february-2026-in-kuala-lumpur